Case Report: Toripalimab: a novel immune checkpoint inhibitor in advanced nasopharyngeal carcinoma and severe immune-related colitis - Luo, Canhua; Chen, Huangwei; Wu, Huihuan; Liu, Yongjia; Li, Guoyin; Lun, Weijian (Frontiers in Immunology, 2023)
Toripalimab, a specific immune checkpoint inhibitor targeting the programmed death 1 (PD-1) receptor, represents a novel immunotherapeutic approach for advanced nasopharyngeal carcinoma, showing promising curative potential. However, it is not without drawbacks, as some patients experience immune-related adverse events (irAEs) associated with this treatment, and there remains a limited body of related research. Here, we present a case of advanced nasopharyngeal carcinoma in a patient who developed colitis as an irAE attributed to Toripalimab. Subsequent to Toripalimab treatment, the patient achieved complete remission. Notably, the development of colitis was accompanied by inflammatory manifestations evident in colonoscopy and pathology results. Further investigation revealed cytomegalovirus (CMV) infection, detected through immunohistochemistry in 11 colon biopsies. Subsequent treatment with ganciclovir and steroids resulted in symptom relief, and colonoscopy indicated mucosal healing. Our case highlights the association between irColitis induced by Toripalimab and CMV infection. Toripalimab demonstrates remarkable efficacy in treating advanced nasopharyngeal carcinoma, albeit with a notable risk of irAEs, particularly in the form of colitis. The link between symptoms and endoscopic pathology findings in irColitis is noteworthy. Standardized biopsy procedures can effectively confirm the diagnosis of CMV infection. Our findings may provide valuable guidance for managing acute CMV infection and irAEs associated with Toripalimab in the treatment of nasopharyngeal carcinoma in the future.